Effectiveness Of Van Hiele Theory-Based STAD Method To Mathematics Learning Outcome - Pramono, Nursiwi Nugraheni, Farid Ahmadi, Rosyad Jati (Elementary School Teacher, 2018)
This study was being underlied by Mathematics learning outcomes of the second grade of SDN Gugus Gajah Mada  which is low. This study was intended to know the effectiveness of STAD model based from van hiele theory  towards  mathematics  subject  learning  achievement  of  the  2nd  grade  students  of  Elementary  Schools (SD) Cluster Gajah Mada Wonogiri. To achieve this objective, this research used quasi experimental research with the type of nonequivalent control group design. The subjects of this study were the 2nd grade students of SD Cluster Gajah Mada Wonogiri. They were sampled by using cluster random sampling. As the data were collected, they were analyzed by using one tailed proportion test, namely z test, t test, gain test and N -gain. The t test shows the comparison of count = 2.98>ttable = 1,68 which meant that Ho is reject, while Ha is accept. The results showed that the mathematics learning achievement of the 2nd grade students of SD Cluster Gajah Mda Wonogiri who achieved the treatment of STAD model based from van hiele theory achieved the passing grade (KKM) score, and STAD model based from van hiele theory than TPS.